MODELS OF CONSEQUENCES OF ACCIDENTS AND DISASTERS IN THE AIRPORT AREA - Запорожець, О. І.; Ахмед, Хайдар Хосейн (Proceedings of National Aviation University (archive), 2021)
Models of damage assessment of buildings and structures, the size of the area of scattering of aircraft wreckage, mortality among the population at the scene of the accident are considered.